Depolymerization of poly(ethylene naphthalate) in fused silica capillary reactor and autoclave reactor from 240 to 280°C in subcritical water. Issue 12 (3rd February 2017) - Bei, Ke; Ma, Peixia; Wang, Junliang; Li, Kai; Lyu, Jinghui; Hu, Zhichao; Chou, I‐Ming; Pan, Zhiyan
Abstract : Depolymerization of poly(ethylene naphthalate) (PEN) in subcritical water was performed in a fused silica capillary reactor (FSCR) and an autoclave reactor. The phase behaviors of PEN in water during the heating‐cooling process in the FSCR were observed under microscope and images were captured by digital camera. Reaction conditions for PEN hydrolysis in the autoclave reactor were chosen based on the experimental results obtained from the FSCR. Under autogenous pressures in the autoclave reactor, the effects of the water/PEN mass ratio (8.0 g/1.0 g to 16.0 g/1.0 g), reaction temperature (240–280°C) and reaction time (5–60 min) on the depolymerization yield and products yields were investigated. The main products of depolymerization were identified and quantified as 2, 6‐naphthalene dicarboxylic acid (2, 6‐NDA) and ethylene glycol (EG). PEN was completely depolymerized at 260°C in 60 min with an optimal water/PEN mass ratio of 12.0 g/1.0 g (12:1). The yields of 2, 6‐NDA and EG were optimized to 83.1% and 79.7%, respectively. Reaction kinetics analysis showed that the PEN depolymerization in subcritical water was first‐order and the activation energy was 95 kJ mol −1 . Additionally, a reaction pathway was proposed based on the experimental results. POLYM. ENG. SCI., 57:1382–1388, 2017. © 2017 Society of Plastics Engineers